2006
DOI: 10.1103/physrevb.73.174507
|View full text |Cite
|
Sign up to set email alerts
|

Classical analysis of phase-locking transients and Rabi-type oscillations in microwave-driven Josephson junctions

Abstract: We present a classical analysis of the transient response of Josephson junctions perturbed by microwaves and thermal fluctuations. The results include a specific low frequency modulation in phase and amplitude behavior of a junction in its zero-voltage state. This transient modulation frequency is linked directly to an observed variation in the probability for the system to switch to its non-zero voltage state. Complementing previous work on linking classical analysis to the experimental observations of Rabi-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…The results presented above rely on the fact that specific initial conditions imposed at the initiation of each sweep of the escape process out of a Josephson junction washboard potential give rise to underdamped oscillations. These oscillations survive coherently throughout the sweep until the switching event takes place, similar to other reported cases [2,20]. We presume that these oscillations are generated by an initial perturbation due to temperature, or recurring cycling of the current sweeps or the perturbation from the onset of the bias sweep itself.…”
Section: Discussionsupporting
confidence: 83%
“…The results presented above rely on the fact that specific initial conditions imposed at the initiation of each sweep of the escape process out of a Josephson junction washboard potential give rise to underdamped oscillations. These oscillations survive coherently throughout the sweep until the switching event takes place, similar to other reported cases [2,20]. We presume that these oscillations are generated by an initial perturbation due to temperature, or recurring cycling of the current sweeps or the perturbation from the onset of the bias sweep itself.…”
Section: Discussionsupporting
confidence: 83%
“…The numerical simulations had shown striking agreement with experimental reality and analytical approaches for ac driven junctions. Thus, three years after the appearance of Martinis and co-workers' paper on the Rabi oscillations, papers were published [48,49] in which it was shown that the features reported in the Martinis Rabi paper could be well interpreted by the nonlinear phenomenology of Josephson junctions. The analytical approximations were in striking agreement with numerical simulations and the experimental results [45,50] as revealed in the lower panel of Fig.35, and by the comparison between analytical ansatz, numerical simulation and experiments shown in Fig.36.…”
Section: Fig 34mentioning
confidence: 99%
“…It is important to pay attention to this profound analogy between the quantum and the classical results in order to separate the macroscopic and quantum modes in mesoscopic systems, which is often a difficult task [ 41 42 ]. Moreover, it seems promising to simulate the behavior of magnetic metamaterials based on artificial Josephson atoms in sufficiently strong fields [ 43 ] using standard classic software designed to study the magnetization reversal processes in large magnetic clusters [ 44 ].…”
Section: Resultsmentioning
confidence: 99%